Participatory modeling to support gender equality. Issue 5 (15th June 2015) - Bleijenbergh, Inge; Van Engen, Marloes
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Interventions to support gender equality in organisations are often unsuccessful. Stakeholders disagree about the causes and problem definition of gender equality or pay lip service to the principle of gender equality, but fail to implement gender equality in practice. The purpose of this paper is to examine participatory modelling as an intervention method to support stakeholders in: reaching a shared problem definition and analysis of gender inequality; and identifying and implementing policies to tackle gender inequality. Design/methodology/approach – The authors apply participatory modelling in case studies on impediments to women's careers in two Dutch universities. Findings – This study shows that participatory modelling supported stakeholders' identification of the self-reinforcing feedback processes of masculinity of norms, visibility of women and networking of women and the interrelatedness between these processes. Causal loop diagrams visualise how the feedback processes are interrelated and can stabilise or reinforce themselves. Moreover, they allow for the identification of possible interventions. Research limitations/implications – Further testing of the causal loop diagrams by quantifying the stocks and the flows would validate the feedback processes and the estimated effects of possible interventions. Practical implications – The integration of the knowledge of researchers and stakeholders in a causal loop diagram supported learning about the issue of gender inequality, hereby contributing to transformative change on gender equality. Originality/value – The originality of the paper lies in the application of participatory modelling in interventions to support gender equality.